Panel vector autoregressive models: a survey - Fabio Canova; Matteo Ciccarelli (European Central Bank (ECB), 2013)
This paper provides an overview of the panel VAR models used in macroeconomics and finance. It discusses what are their distinctive features, what they are used for, and how they can be derived from economic theory. It also describes how they are estimated and how shock identification is performed, and compares panel VARs to other approaches used in the literature to deal with dynamic models involving heterogeneous units. Finally, it shows how structural time variation can be dealt with and illustrates the challanges that they present to researchers interested in studying cross-unit dynamics interdependences in heterogeneous setups.
Keywords: C11; C30; C53; 330; estimation; Identification; inference; Panel VAR; Panel; VAR-Modell; Bayes-Statistik; Theorie